ORGANIZATIONAL CULTURE AND DIGITAL TRANSFORMATION OF MSMES: BIBLIOMETRIC AND SYSTEMATIC LITERATURE ANALYSIS - Rahawarin, Fazlur Rahman; Mukhlis, Imam; Murwani, F. Danardana (PUSAT KEWIRAUSAHAAN UNIVERSITAS BALIKPAPAN, 2023)
Digital transformation and organizational culture have an interesting relationship to research. The growing adaptation of technology depends on how good the culture in an organization is. Likewise, MSME players also need digital transformation in developing their business. Various studies have been conducted in understanding the relationship between organizational culture and digital transformation but have experienced inconsistencies. This article discusses how previous research explains the relationship. systematic literature review and bibliometric analysis have been used in this study to explore how far researchers get results from the relationship between culture and digital transformation